PENGARUH TEAMWORK, DISIPLIN KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN :Studi di Rumah Sakit X Jakarta Selatan - Latifah Intan Safitri (2021)
This research is a quantitative research with the aim of knowing the effect of teamwork, work discipline, organizational climate on employee performance. By making permanent employees of the General Hospital as the population in this study, as many as 187 people with a non-probability sampling technique using convenience sampling, based on the Slovin formula, a sample of 130 respondents was obtained. Data processing used IBM SPSS Statistics 23 program with a significance level of 5% (0.05). The results of the hypothesis test show that (1) teamwork partially has an influence on employee performance, (2) work discipline partially has an influence on employee performance, (3) organizational climate partially has an influence on employee performance, (4) simultaneous teamwork , work discipline, and organizational climate have an influence on employee performance. Employee performance is influenced by 77.7% by teamwork, work discipline and organizational climate.